Discovery of two distinct types of equatorial 150 km radar echoes. Issue 17 (9th September 2013) - Chau, J. L.; Kudeki, E.
<x xml:space="preserve">Abstract</x> [1] We show here that VHF signals scattered from the 150 km region above Jicamaca exhibit two distinct types of features. In one type (type A), the Doppler spectral width increases with the echo strength and the corresponding signal‐to‐noise ratio (SNR). A second type (type B) of higher SNR echoes exhibits SNR‐independent Doppler spectral widths that are much narrower than those observed in the first type. The type A echo population is by far the dominant population. Comparisons with earlier data sets collected at Jicamarca and elsewhere suggest that the type A and type B are likely to be associated with a naturally enhanced incoherent scattering (NEIS) process and the unstable growth of field‐aligned irregularities (FAIs), respectively. We conjecture that small radar systems operated near the geomagnetic equator that have reported 150 km echo observations detected FAI echoes and that the NEIS echoes can only be seen by high sensitivity systems.